Principal Management in Improving Organization Performance at SMA Darul Abrar and Nurul Huda Al Aziziyyah in Aceh Jaya Regency - Wahyuni, Andri; Murniati, Murniati; Usman, Nasir (Jurnal Pendidikan Progresif, 2021)
This research aims to comprehend the implementation of principal managerial role in improving organizational performance at two private high schools in Aceh Jaya Regency. Data collected through the interview guidelines and documentations. The subject of this research is the principal, supervisor, and teachers working at the Darul Abrar and Nurul Huda Al Aziziyyah private high school Aceh Jaya. The result shows that: (1) for planning function, principal participates with teachers in planningthe learning process. In the management standard, principal formulates the visions-mission, the purpose, and the work plan ofthe school; (2)for organizing function, the principal gives assignments and responsibilities for each teacher. This function emphasizes on creating organizational structure, main tasks, and function; (3) for the implementing function, the principal motivate the teachers to become more enthusiastic in teaching. In the standard, principal’s function is to provide a clear instruction; (4)in supervising function, principal evaluates the execution of tasks and responsibilities according to specific organizational structure. Keywords: principal management, organizational performance, qualitative research. DOI: http://dx.doi.org/10.23960/jpp.v11.i2.202101